2016
DOI: 10.1371/journal.pone.0165987
|View full text |Cite
|
Sign up to set email alerts
|

Networks Depicting the Fine-Scale Co-Occurrences of Fungi in Soil Horizons

Abstract: Fungi in soil play pivotal roles in nutrient cycling, pest controls, and plant community succession in terrestrial ecosystems. Despite the ecosystem functions provided by soil fungi, our knowledge of the assembly processes of belowground fungi has been limited. In particular, we still have limited knowledge of how diverse functional groups of fungi interact with each other in facilitative and competitive ways in soil. Based on the high-throughput sequencing data of fungi in a cool-temperate forest in northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 81 publications
(111 reference statements)
6
44
1
Order By: Relevance
“…Recalcitrant residues of EcM and ErM fungal cell walls contribute much to boreal forest humus (Clemmensen et al ., ), especially when complexed with root‐derived tannins (Adamczyk et al ., ). While the EcM fungal mycelium proliferates in organic soil horizons (Lindahl et al ., ), the AM fungal mycelium is mostly distributed in upper mineral soil layers (interpretation of data in Toju et al ., ) in forest ecosystems. Collectively, these studies suggest that residues of EcM and ErM fungi result in recalcitrant C accumulation mainly in topsoil, whereas both EcM and AM fungi contribute to C stored in mineral soil horizons.…”
Section: Soil Processesmentioning
confidence: 99%
“…Recalcitrant residues of EcM and ErM fungal cell walls contribute much to boreal forest humus (Clemmensen et al ., ), especially when complexed with root‐derived tannins (Adamczyk et al ., ). While the EcM fungal mycelium proliferates in organic soil horizons (Lindahl et al ., ), the AM fungal mycelium is mostly distributed in upper mineral soil layers (interpretation of data in Toju et al ., ) in forest ecosystems. Collectively, these studies suggest that residues of EcM and ErM fungi result in recalcitrant C accumulation mainly in topsoil, whereas both EcM and AM fungi contribute to C stored in mineral soil horizons.…”
Section: Soil Processesmentioning
confidence: 99%
“…Nevertheless, due to the limitations in the detection methods and the complexity of microbial metabolic pathways, information on the microbial functional properties in response to liming in sugarcane cultivation is limited. Based on high-throughput sequencing data, FUNGuild and PICRUSt have recently been developed as highly encouraging tools to predict functionality in fungal and bacterial communities [25,26]. PICRUSt has been used in the medical field to predict the consequences of diseases and drugs on human/animal bacterial metabolism [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Quilliam et al (2013) demonstrated that biochar pores can effectively protect fungi against competitors. Further, Abel et al (2013) indicated that biochar can improve the habitat for microbes by improving the physical properties of soils, and promote cooperative relationships among microorganisms, that then allow for good utilization of soil resources (Toju et al, 2016). In addition to soil pH was found to significantly influence fungal interactions in RS + biochar (p < 0.001; Fig.…”
Section: Increased Interactions Among Soil Fungimentioning
confidence: 94%
“…Saprophytic fungi, which inhabit the rhizosphere, are largely distributed in three phyla: Zygomycota, Ascomycota, and Basidiomycota. Saprophytic fungi can control the cycling rate of nutrients in agricultural ecosystems and promote the decomposition of organic matrices (Toju et al, 2016). Solaiman et al (2010) found that saprophytic fungi are convenient to grow in biochar due to their hyphal structures and highly active exoenzymes.…”
Section: Increased Interactions Among Soil Fungimentioning
confidence: 99%